Composition analysis of fatty acids and stereo-distribution of triglycerides in human milk from three regions of China. (July 2020) - Chen, Y.J.; Zhou, X.H.; Han, B.; Li, S.M.; Xu, T.; Yi, H.X.; Liu, P.; Zhang, L.W.; Li, Y.Y.; Jiang, S.L.; Pan, J.C.; Ma, C.H.; et al.
Graphical abstract: Highlights: The total fatty acids composition was easily influenced by different regions. But the preference distribution of fatty acids was hardly affected by regions. SCFA and MCFA were mainly esterified at sn -3 position, but LCSFA on the contrary. Compared to MUFA, PUFA were more likely esterified at sn -3 position. Abstract: Understanding the components composition characteristics of human milk is conductive for the development of infant formulas. The total fatty acids composition and the stereo-distribution of fatty acids in human milk triglycerides (TGs) from three regions (Zhengzhou, Wuhan and Harbin) of China were analyzed. The total and intrapositional fatty acids composition of human milk TGs showed significant differences among three regions. Zhengzhou, Harbin and Wuhan human milk possessed highest levels of medium-chain fatty acids (MCFA, 6.36 ± 1.46%), short-chain fatty acids (SCFA, 0.10 ± 0.03%) and monounsaturated fatty acids (MUFA, 34.61 ± 0.45%), and polyunsaturated fatty acids (PUFA, 30.34 ± 0.33%), respectively. The preference distribution of fatty acids in human milk TGs was hardly affected by regions, for the relative conservative interpositional levels of each fatty acids in three regions. Not only the specific distribution of sn -2 position, but the esterification of fatty acids in sn -1 and sn -3 positions also had preference. SCFA and MCFA were mainly esterified at sn -3 position, but LCSFA most unlikely distributed at the sn -3 position. The preference esterification of MUFA were sn -1, sn -3 >  sn -2, and PUFA were sn -3 >  sn -1 >  sn -2. Therefore, the optimization of infant formulas not only needs considering total fatty acid composition of TGs but requires thinking over the stereo-distribution of fatty acids.